Whole-body vibration as an effective sports competition warm-up: a randomized controlled trial in a young and healthy population - Amato, Alessandra; Petrigna, Luca; Amorim, Paulo Roberto dos Santos; Wenxin, Xu; Musumeci, Giuseppe (Frontiers in Physiology, 2026)
IntroductionThe long-term effect of training with Whole-Body Vibration (WBV) has been documented to have benefits on health, but its acute role in performance remains unclear. This study evaluated whether a 5-minute WBV warm-up could serve as an effective warm-up to optimize sport performance.MethodsNinety-three participants healthy, active but not professional athletes, (23.6 ± 5.7 years) were randomized into three groups: control (CG), sham vibration group (SVG), and vibration group (VG). All participants completed tests at two time points (T0 and T1): countermovement jump (CMJ) the primary outcome, reaction time (RT), reactive strength index (RSI), and sit-and-reach (SRT). During assessments, superficial electromyography (sEMG) was recorded to explore potential neuromuscular changes associated with the interventions. Between T0 and T1, the VG performed a 5-minute WBV warm-up, the SVG completed the same warm-up without vibration, and the CG remained at rest.ResultsVG improved in the primary outcome, CMJ (p < 0.01), SRT (p < 0.01), and RT (p < 0.01), while RSI remained unchanged (p > 0.05). SVG showed similar improvements (CMJ (p < 0.01), SRT (p < 0.01), and RT (p < 0.01), RSI (p > 0.05), whereas CG experienced a decline in RSI (p < 0.05). Between-group contrasts at the post-test endpoint for the primary outcome (CMJ) showed no statistical significance (all p > 0.05), a finding consistent across all other variables.ConclusionThe proposed 5-minute warm-up protocol, whether performed with or without whole-body vibration, effectively enhanced performance in sport-related tests without inducing a performance decrease. However, WBV did not provide additional benefits over the same warm-up performed without vibration.